Von der Dämonologie zum Unbewussten. Die Transformation der Anthropologie um 1800 - Zander, Helmut; Sziede, Maren (2015)
As the science of man, anthropology was among the most exciting disciplines during the period of intense change from the early modern era to modernity. Where demons had once wielded their power, after 1800, it was now the unlimited shoals of the subconscious that were disseminated. Or did they actually stay right next to each other and within one another?